Handbook of fruit and vegetable flavors - Hui, Y. H. (Yiu H.) (Wiley, 2010)
"Acting as chemical messengers for olfactory cells, food flavor materials are organic compounds that give off a strong, typically pleasant smells. Handbook of Fruit and Vegetable Flavors explores the flavor science and technology of fruits and vegetables, spices, and oils by first introducing specific flavors and their commercialization, then detailing the technical aspects, including biology, biotechnology, chemistry, physiochemistry, processing, analysis, extraction, commodities, and requirements for application as food additives. With chapter authors representing more than ten different countries, this handy reference provides a comprehensive view of this evolving science."--